Distribution of Thottea grandiflora and Goniothalamus macrophylus in UiTM Jengka forest reserve / Ishak Ibrahim, Mohd Faiz Aznan and Mohd Raziman Abd Rahim - Ibrahim, Ishak; Aznan, Mohd Faiz; Abd Rahim, Mohd Raziman (2008)
The UiTMJFR is a forest reserve in Pahang with about 250 acres. This study was recorded the distribution of Hempedu Beruang (Thottea grandiflora) and Gajah Beranak (Goniothalamus macrophylus) in UiTMJFR from Line 1 till Line 20. UiTM has many type of herb, but we just choose 2 from them because of timing factor. From this study it was found 524 and 151 no of individual for Hempedu Beruang and Gajah Beranak respectively. Gajah Beranak is the most found in UiTM Jengka because it easily growth in lowland and expose to sunshine. For Hempedu Beruang, usually we found it with height 41-60 (cm) and for Gajah Beranak is more then 100cm.